Gaseous nitrous acid (HONO) and nitrogen oxides (NOx) emission from gasoline and diesel vehicles under real-world driving test cycles. (3rd April 2017) - Trinh, Ha T.; Imanishi, Katsuma; Morikawa, Tazuko; Hagino, Hiroyuki; Takenaka, Norimichi
ABSTRACT: Reactive nitrogen species emission from the exhausts of gasoline and diesel vehicles, including nitrogen oxides (NOx ) and nitrous acid (HONO), contributes as a significant source of photochemical oxidant precursors in the ambient air. Multiple laboratory and on-road exhaust measurements have been performed to estimate the NOx emission factors from various vehicles and their contribution to atmospheric pollution. Meanwhile, HONO emission from vehicle exhaust has been under-measured despite the fact that HONO can contribute up to 60% of the total hydroxyl budget during daytime and its formation pathway is not fully understood. A profound traffic-induced HONO to NOx ratio of 0.8%, established by Kurtenbach et al. since 2001, has been widely applied in various simulation studies and possibly linked to under-estimation of HONO mixing ratios and OH radical budget in the morning. The HONO/NOx ratios from direct traffic emission have become debatable when it lacks measurements for direct HONO emission from vehicles upon the fast-changing emission reduction technology. Several recent studies have reported updated values for this ratio. This study has reported the measurement of HONO and NOx emission as well as the estimation of exhaust-induced HONO/NOx ratios from gasoline and diesel vehicles using different chassis dynamometer tests under various real-world driving cycles. For the tested gasoline vehicle, which was equipped with three-way catalyst after-treatment device, HONO/NOx ratios ranged from 0 to 0.95 % with very low average HONO concentrations. For the tested diesel vehicle equipped with diesel particulate active reduction device, HONO/NOx ratios varied from 0.16 to 1.00 %. The HONO/NOx ratios in diesel exhaust were inversely proportional to the average speeds of the tested vehicles. Implications : Photolysis of HONO is a dominant source of morning OH radicals. Conventional traffic-induced HONO/NOx ratio of 0.8% has possibly linked to underestimation of the total HONO budget and consequently underestimation of OH radical budget. The recently reported HONO/NOx ratio of ~1.6% was used to stimulate HONO emission, which resulted in increased HONO concentrations during morning peak hours and its impact of 14% OH increment in the morning. However, the results were still lower than the measured concentrations. More studies should be conducted to establish an updated traffic-induced HONO/NOx ratio.